Older Adults’ Internet Use for Health Information: Digital Divide by Race/Ethnicity and Socioeconomic Status - Yoon, Hyunwoo; Jang, Yuri; Vaughan, Phillip W.; Garcia, Michael (Journal of applied gerontology, 2020)
Building upon literature suggesting low Internet use among racial/ethnic minorities and socioeconomically disadvantaged groups, this study examined how race/ethnicity and socioeconomic status (SES) influence the Internet use for health information, addressing both independent and interactive effects. Using data from 17,704 older adults in the California Health Interview Survey, logistic regression models were estimated with race/ethnicity (Whites, African Americans, Latinos, and Asians), SES index, and the interaction between race/ethnicity and SES index. Overall, approximately 40% of participants were Internet-users for health information. Direct effects of race/ethnicity and SES—and their interactions—were all found to be significant. Minority status combined with the lowest levels of SES substantially reduced the odds of using Internet for health information. Findings suggest the combination of racial/ethnic minority status and low SES as a source of digital divide, and provide implications for Internet technology training for the target population.